Backstepping Control for a Tandem Rotor UAV Robot with Two 2-DOF Tiltable Coaxial Rotors - Xiongshi Xu; Keigo Watanabe; Isaku Nagai (Journal of Robotics and Control (JRC), 2021)
The study of a fully actuated multi-rotor UAV robot is very important in the field of infrastructure inspection because it needs a dexterous motion, such as hovering in a special fixed attitude, etc. This paper presents a backstepping control method for a simplified fully actuated model of a tandem-rotor UAV robot with two 2-DOF tiltable coaxial rotors. A MIMO vectorial backstepping approach is adopted here because the input distribution matrix is a square and nonsingular matrix. The two-stage control method based on the Lyapunov second method is presented to stabilize the position and attitude of the whole system. The static control allocation problem is also solved by using a Moore-Penrose pseudo-inverse. Finally, two simulations are demonstrated to verify the performance of the proposed control method, where one is a stabilizing problem in which all the desired position and attitude are to be constant, whereas the other is a trajectory tracking problem in which the desired positions are time-varying while the desired attitudes are to be constant.